Centro de serviços compartilhados (CSC) versus estruturas locais de compartilhamento: um estudo no sistema SICREDI - Agazzi, Cléber Alexandre (Universidade do Vale do Rio dos Sinos, 2018)
Many companies have adopted a strategy of centralized services as a way of organizing back office activities, seeking a reduction of costs and improving the overall efficiency of operations. This strategy of centralization can follow different trajectories, which vary in degree of consolidation. Following paths that lead to a lower level of consolidation means that one cannot sow the maximum gains of scale, one of the main factors of a cost efficient strategy. In this sense, the present study seeks to comprehend why, in a system of credit unions, some credit unions choose to develop local structures in order to centralize services, instead of using the structure of the shared service center (SSC) available to all the system through it’s “confederation”, abdicating in part in gains related to scale. By using a descriptive qualitative case study, executives of credit unions and of the “confederation” were interviewed and, after analyzing this content, it was possible to demonstrate that there is rationality behind the strategy adopted by the credit unions, taking into consideration that models found during the bibliographical review can support this statement. Beyond the central theme of the study, the bibliographical review addressed themes related to the context in which the object organization is inserted, which aided in the comprehension and revealed some distinct factors of this type of organization, which also influenced the scenario. Within an academic perspective, the study fills gaps of research when applying a model of analysis, developed in another country, to a private company in Brazil. In an overall perspective, the study provides important information and presents a tool that can be used in strategic definitions about centralizing services.
Keywords: Back office; Serviços compartilhados; Centro de serviços compartilhados; Cooperativas de crédito; Back office; Shared services; Shared service centers; Credit unions; ACCNPQ::Ciências Sociais Aplicadas::Administração